The first year of implementing a new concept of the journal "Mining of Mineral Deposits" of the National Mining University - Lozynskyi, V.; Sai, K.; Vvedenska, T. (Розробка родовищ, 2017)
This article presents the analysis of Ukrainian mining sciences journal – “Mining of Mineral Deposits” (English acronym – MMD). Our paper presents a case study of a journal in the field of mining sciences and describes the first year of implementing a new concept of the journal. The results can serve as a reference in future studies of the jour-nal in a new form. The findings of future research may be an indication as to whether the adopted policy of interna-tionalization of the journal is effective and increases the impact of the Journal in World Science. Special considera-tion is given to website visitors activity and visits frequency statistics. It appears that MMD is improving its position within the group of leading and original Ukrainian mining periodicals. В данной статье произведен анализ украинского журнала в области горной науки – “Разработка месторожде-ний” (аббревиатура на английском языке “MMD”). Статья представляет собой анализ конкретного горного журнала и описывает первый год имплементации его новой концепции. Полученные результаты могут стать сравни-тельным ориентиром при проведении дальнейшего анализа. Результаты данного исследования направлены на определение соответствия принятой политики интернационализации журнала в международном научном про-странстве. Особое внимание уделяется активности посещений сайта журнала. В результате проведенного анализа можно утверждать, что журнал “Разработка месторождений” усиливает свои позиции среди ведущих украинских периодических изданий горного профиля. У даній статті наведено аналіз українського журналу в області гірничої науки – “Розробка Родовищ” (абревіатура англійською мовою “MMD”). Стаття представляє собою аналіз конкретного гірничого журналу й описує перший рік імплементації його нової концепції. Отримані результати можуть стати порівняльним орієнти-ром при проведенні майбутнього аналізу. Результати даного дослідження спрямовані на визначення відповідності прийнятої політики інтернаціоналізації журналу в міжнародному науковому просторі. Особлива увага приділяється активності відвідувань сайту журналу. В результаті проведеного аналізу можна стверджувати, що журнал “Розробка Родовищ” посилює свої позиції серед провідних українських періодичних видань гірничого профілю.